The Accessibility of Multifunction Printers: An Updated Usability Study of Accessible Multifunction Printers and a Survey of Multifunction Printer Users with Vision Loss. (January 2016) - Packer, Jaclyn; Reuschel, William
Introduction: This article investigates the use of multifunction printers by individuals with vision loss, and explores current accessibility solutions to determine the extent of accessibility and usability for those who are visually impaired, with suggestions for improvement. Methods: A usability study conducted in early 2014 recruited 10 volunteers with varied degrees of vision loss and user experience. Each performed four tasks on the Lexmark, Canon, and Ricoh multifunction printer accessibility solutions. An online survey conducted between October 2011 and April 2012 used a volunteer sample recruited through advertising and distribution in private organizations. The sample consisted of 26 individuals who were blind and 34 who had low vision; all participants had experience using multifunction printers. The sample was comprised of 58% women, 83% white, and 78% college graduates. The median age range was 45 to 54 years old. Results: The usability study respondents had a high success rate in performing tasks, averaging a rating of 4.5 out of 5, and scores increased over the four tasks. Participants preferred the Lexmark machine due to its familiar QWERTY keyboard interface. Most survey respondents (80%) use a multifunction printer at home for personal use; 67% use multifunction printers in the workplace. Fifty-eight percent used assistive technology with their multifunction printers. The most important multifunction printer function was printing, followed by scanning and copying. Faxing was least important. Those with low vision were more likely to use the multifunction printer's copy function than those who were blind ( p < .002). To improve accessibility, respondents suggested higher contrast, larger characters, speech output, and tactile controls. Discussion: People with vision loss use multifunction printers at work and home. Current accessibility solutions for multifunction printers work well for individuals with vision loss, but there is much room for improvement. Manufacturers should be urged to implement suggestions from research participants to increase the accessibility of their products.